Financial Locus of Control and Life Satisfaction: Financial Resilience the Moderator - Dr Zia Khalid; Dr Zafar Azam; Dr Aftab Hussain Tabasam (Social Science Review Archives, 2025)
Economic meltdown will continue hurling financial panics in lives of many. Financial issues are hard to tackle. The fire of financial troubles can easily destroy life satisfaction. Anywhere a person is financially unsound, miseries naturally flow into life. Irrespective of everything that matters in the eyes of ordinary people, the truly blessed is one who is content with life and not complaining and castigating it. The time that is otherwise spent on thinking and discussing about problems of life can be better utilized by satisfied people for societal/organizational purposes. That is why life satisfaction is achieving a universal status and it is difficult to shrug off shoulders from such an important parameter of quality life. Financially resilient people are believed to brush aside pains of financial pressures and get along with them. It can result into grater life satisfaction. Thus, those financially satisfied will be able to spend a satisfied life and hence their societies/organizations can reap scores of benefits. Those possessing greater locus of control are considered to be having that very financial resilience. A proposed way to diffuse financial shocks is to invest in locus of control. It will improve resilience and hence a better part, life satisfaction, will emerge. Those with locus of control do not give away their control to external forces and hence it is likely that they will have a more life satisfaction. But certainly it is still hypothetical and as long as empirical evidence is missing management/government can't stress on developing financial resilience. The conceptual model actually provides a viable guideline for future research scholars to implement it empirically to see how far it can help in realizing life satisfaction. For business organizations, an apt audience for future scholar could be frontline employees, a major pillar of services marketing, who are particularly vulnerable to economic shocks.